2021
DOI: 10.1111/ocr.12485
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic assessment of infrazygomatic crest bone depth for extra‐alveolar miniscrew insertion in subjects with different vertical and sagittal skeletal patterns

Abstract: Objective To evaluate bone availability at the infrazygomatic crest for extra‐alveolar bone miniscrew insertion in subjects with different vertical and sagittal skeletal patterns. Setting and sample population Measurements of the infrazygomatic crest were performed on multislice computed tomography scans from 58 adults with different skeletal patterns. Materials and methods Infrazygomatic crest bone depth was measured at 4, 5 and 6 mm from the cementoenamel junction (CEJ) of the maxillary first molar at three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Besides the insertion region, the height of the insertion and the gingival slope can directly affect bone depth [ 9 ]. We found that as the height of the insertion increased, bone depth tended to decrease and the ratio of bone deficiency increased, which was in agreement with previous studies [ 12 , 16 , 17 ]. Regarding soft tissue, high degree of insertion at the alveolar mucosa will frequently cause mucosal inflammation, soft tissue embedment, or patient discomfort.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Besides the insertion region, the height of the insertion and the gingival slope can directly affect bone depth [ 9 ]. We found that as the height of the insertion increased, bone depth tended to decrease and the ratio of bone deficiency increased, which was in agreement with previous studies [ 12 , 16 , 17 ]. Regarding soft tissue, high degree of insertion at the alveolar mucosa will frequently cause mucosal inflammation, soft tissue embedment, or patient discomfort.…”
Section: Discussionsupporting
confidence: 93%
“…Although few studies have investigated the bone depth in the U7M region, thicker buccal alveolar bone has been reported [ 21 , 27 ], which can probably explain our findings. Previous studies considered U6 as a common region for insertion in the IZC [ 9 , 12 , 14 , 16 ], but in recent years, growing research has focused on region U67 instead for rich bone mass [ 17 , 18 , 20 ]. However, there is a risk that the miniscrew might injure or block the root of U6 if it is inserted into the narrow radicular region of U67, especially during the molar distalization movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the palate, distance to the nasal cavity and maxillary sinus was greatest in the region mesial to the first premolar and then the distance started to decrease significantly [36]. In the buccal area, perpendicular insertion was safe with minimal risk of sinus or nasal cavity injury, while oblique placement increased the possibility of sinus and Schneiderian membrane penetration [36][37][38].…”
Section: Perforation Of Maxillary Sinus and Nasal Cavity Floormentioning
confidence: 99%
“…Miranda-Viana et al 14 observed that there are different morphological patterns of the hard palate; thus, knowledge about the skeletal patterns can provide information for orthodontic and surgical interventions. Studies using CT have shown that vertical and sagittal facial skeletal patterns can influence the anatomy of certain bone structures that are insertion sites for orthodontic miniscrews, such as the mandibular symphysis, 15 alveolar and cortical bone, 16 infrazygomatic crest 17,18 and buccal shelf. 19 To the best of our knowledge, no study evaluated the relationship between hard palate thickness and different skeletal patterns aiming the MARPE miniscrew insertion.…”
mentioning
confidence: 99%